2017
DOI: 10.1007/s11481-017-9744-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Surface CB2 Receptor during Human B Cell Activation and Differentiation

Abstract: Cannabinoid receptor type 2 (CB2) is the primary receptor pathway mediating the immunologic consequences of cannabinoids. We recently reported that human peripheral blood B cells express CB2 on both the extracellular membrane and at intracellular sites, where-as monocytes and T cells only express intracellular CB2. To better understand the pattern of CB2 expression by human B cells, we examined CD20+ B cells from three tissue sources. Both surface and intracellular expression were present and uniform in cord b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…In addition, polar ligands may have reduced access to intracellular receptor populations due to a reduced propensity to cross the plasma membrane in comparison with more lipophilic ligands ( Liu et al, 2011 ). Indeed, CB 2 has been reported to be expressed both at the cell surface and intracellularly ( Kleyer et al, 2012 ; Brailoiu et al, 2014 ; Castaneda et al, 2017 ), and intracellular CB 2 may be able to activate distinct signalling responses from surface CB 2 ( Brailoiu et al, 2014 ). Thus ligands that differentiate between these populations would have the potential to induce differential signalling patterns in comparison with lipophilic ligands that can interact with both surface and intracellular receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polar ligands may have reduced access to intracellular receptor populations due to a reduced propensity to cross the plasma membrane in comparison with more lipophilic ligands ( Liu et al, 2011 ). Indeed, CB 2 has been reported to be expressed both at the cell surface and intracellularly ( Kleyer et al, 2012 ; Brailoiu et al, 2014 ; Castaneda et al, 2017 ), and intracellular CB 2 may be able to activate distinct signalling responses from surface CB 2 ( Brailoiu et al, 2014 ). Thus ligands that differentiate between these populations would have the potential to induce differential signalling patterns in comparison with lipophilic ligands that can interact with both surface and intracellular receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the cannabinoids’ effects on T cell function and development, Yuan et al demonstrated that Δ 9 -THC regulates Th1/Th2 cytokine balance in activated human T cells [ 211 ]. B cells are another immune cell population whose differentiation depends on ECS components such as CB 2 receptors [ 177 , 178 ].…”
Section: The “Immune Endocannabinoid System” In Adaptive and Innatmentioning
confidence: 99%
“…There are also various explanations for potential dual coupling within the same cell. Signalsome subcellular compartmentalization and/or sequestration of signaling components is one example reviewed in 60 ; indeed subcellular distribution of CB2 can influence CB2 signaling patterns 6 , and CB2 seems to have a particularly unique distribution in immune cells [61][62][63] . Homologous signaling feedback upon CB2 activation which results in rapid desensitization of Gαs coupling with little or slower influence on Gαi coupling such as via differential phosphorylation by G Protein-Coupled Receptor Kinases or PKA 64-66 might assist in explaining the observed cAMP signaling profile.…”
Section: Discussionmentioning
confidence: 99%